2012
DOI: 10.1093/humrep/der461
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline and neutral Comet assay profiles of sperm DNA damage in clinical groups

Abstract: Comet assay profiles, applied to different clinical groups, may be useful for determining prognosis in cases of male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 1 publication
11
102
3
1
Order By: Relevance
“…Since the OTM values at pH [ 13 were 5.1-15.3 times higher than those at pH 12.1, we deduce that compared with the DNA strand breaks, ALS was the main type of DNA damage produced by monocrotophos exposure. As the neutral comet assay was reported to be more specific for the detection of DSB (Shahidi et al 2007;Cortés-Gutiér-rez et al 2012;Ribas-Maynou et al 2012) and the OTM values at pH 12.1 were 4.9-31.5 times higher than those at pH 8.2-8.5, it was predominantly SSB with much fewer DSB detected by the pH 12.1 comet assay in this study. Consistently, Tice et al (2000) suggested that almost all genotoxic agents induce SSB orders of magnitude more than DSB.…”
Section: Discussionsupporting
confidence: 49%
“…Since the OTM values at pH [ 13 were 5.1-15.3 times higher than those at pH 12.1, we deduce that compared with the DNA strand breaks, ALS was the main type of DNA damage produced by monocrotophos exposure. As the neutral comet assay was reported to be more specific for the detection of DSB (Shahidi et al 2007;Cortés-Gutiér-rez et al 2012;Ribas-Maynou et al 2012) and the OTM values at pH 12.1 were 4.9-31.5 times higher than those at pH 8.2-8.5, it was predominantly SSB with much fewer DSB detected by the pH 12.1 comet assay in this study. Consistently, Tice et al (2000) suggested that almost all genotoxic agents induce SSB orders of magnitude more than DSB.…”
Section: Discussionsupporting
confidence: 49%
“…% Tail DNA represented a threshold value of 15 % for predicting male infertility with an area under the curve 0,837 and Tail Moment represented a threshold value of 15,21 % with an area under the curve 0,796. However, these results are not comparable with previous studies because it is not mentioned which comet measurement were used in these studies [15,18,31]. Higher area under the ROC curve has been shown by % Tail DNA with a high sensitivity and specificity of 0,717 and 0,800 respectively (Table 1, Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…According to the same authors, DNA damage in those spermatozoa derives mainly from nuclease activity (35). Of interest, we recently demonstrated that the percentage of dimmer spermatozoa correlates with those of activated caspases and semen apoptotic bodies, also indicating that their damage is due to apoptotic nucleases (26).…”
Section: Figurementioning
confidence: 78%